Comparison of laparoscopic closure of the bladder with barbed polyglyconate versus polyglactin suture material in the pig bladder model: an experimental in vitro study - Gözen, Ali Serdar; Schulze, Michael; Rassweiler, Jens (Journal of endourology, 2012)
Purpose: The objective of this randomized in-vitro study was to compare the suturation time, integrity, and quality of the bladder closure in fresh cadaver pig bladders performed with barbed polyglyconate sutures vs polyglactin 910 sutures in running and interrupted fashion.Materials and Methods: Forty-eight pig bladders, each weighing from 120 to 150 g, were randomly divided into three groups: Group 1 (interrupted polyglactin 910 suture group), group 2 (running polyglactin 910 suture group), and group 3 (running barbed polyglyconate suture group). The bladder defects were closed laparoscopically, and the suturation times were noted. Two surgeons evaluated the integrity of each bladder closure. A cystometry was performed, and the filling and leak pressures were noted. A Kruskal-Wallis variance analysis test was used to compare the results of the three groups, and P<0.05 was considered significant.Results: There was a statistically significant difference between the mean suturation times of three groups: Group 1, 15.2 minutes; group 2, 9.14 minutes; and group 3, 7.13 minutes (P<0.05). Mean bladder capacity at the time of leakage was 276.2, 353.8, and 419.7 mL for groups 1, 2, and 3, respectively, and the difference was statistically significant (P<0.05).Conclusion: For the first time, we demonstrated laparoscopic knotless closure of bladder defects using the barbed polyglyconate suture material in an experimental in-vitro model. Closing the pig bladder with running knotless barbed suture provides a more effective and faster watertight bladder closure than traditional polyglactin 910 suture material.
Online ahead of print: October 18, 2011
Gesehen am 06.12.2018